2013
DOI: 10.1007/s00454-013-9495-z
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Constructions of Centrally Symmetric $$k$$ -Neighborly Polytopes and Large Strictly Antipodal Sets

Abstract: We present explicit constructions of centrally symmetric 2-neighborly d-dimensional polytopes with about 3 d/2 ≈ (1.73) d vertices and of centrally symmetric k-neighborly d-polytopes with about 2 3d/20k 2 2 k vertices. Using this result, we construct for a fixed k ≥ 2 and arbitrarily large d and N , a centrally symmetric d-polytope with N vertices that has at least 1 − k 2 · (γ k ) d N k faces of dimension k − 1, where γ 2 = 1/ √ 3 ≈ 0.58 and γ k = 2 −3/20k 2 2 k for k ≥ 3. Another application is a constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Talata improved this by a construction (described in [31, Lemma 9.11.2]) to A (d) Ω(3 d/3 ), and announced that A (d) Ω(5 d/4 ) (see [31, p. 271]). Subsequently, Barvinok, Lee, and Novik [15] found another construction that shows A (d) Ω(3 d/2 ). This is currently the best-known bound for e(X d ) for strictly convex spaces.…”
Section: Equilateral Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Talata improved this by a construction (described in [31, Lemma 9.11.2]) to A (d) Ω(3 d/3 ), and announced that A (d) Ω(5 d/4 ) (see [31, p. 271]). Subsequently, Barvinok, Lee, and Novik [15] found another construction that shows A (d) Ω(3 d/2 ). This is currently the best-known bound for e(X d ) for strictly convex spaces.…”
Section: Equilateral Setsmentioning
confidence: 99%
“…Makai and Martini [122] showed that a (3) 3, and conjectured that equality holds. Barvinok, Lee, and Novik [15] showed that a (d) Ω(3 d/2 ). The best upper bound known is the almost trivial a (d) 2 d − 1.…”
Section: Brass Conjectured That Dmentioning
confidence: 99%
“…The best earlier lower bound was 3 ⌊d/2⌋−1 − 1 due to Barvinok, Lee and Novik [2]. Note that the same upper bound (2 d − 1) holds for strictly antipodal sets as well [3].…”
Section: Introductionmentioning
confidence: 89%
“…Motivated by establishing an upper bound theorem for centrally symmetric polytopes (which is an open problem, even for 4‐dimensional polytopes), Barvinok and Novik employed symmetric moment curves to define a centrally symmetric analogue of cyclic polytopes, called bicyclic polytopes . They used bicyclic polytopes to give lower bounds on the numbers of faces of centrally symmetric polytopes, which they and Lee improved with polytopes constructed from variants of the symmetric moment curve. We refer to the survey of Novik for a detailed discussion of this topic.…”
Section: Related Workmentioning
confidence: 99%